2020
DOI: 10.1111/jofi.12896
|View full text |Cite
|
Sign up to set email alerts
|

Bank Quality, Judicial Efficiency, and Loan Repayment Delays in Italy

Abstract: Italian rms delay payment to banks weakened by past loan losses. Exploiting Credit Register data, we fully absorb borrower fundamentals with rm-quarter eects; thus, identication reects rm choices to delay payment to some banks but not others, depending upon their health. This selective delay occurs more where legal enforcement of collateral recovery is slow. Poor enforcement encourages borrowers not to pay, once the value of their bank relationship comes into doubt. Selective delays occur even by rms able to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 61 publications
0
17
0
1
Order By: Relevance
“…A recent study by Miroshnychenko, bozziy and barontini (2019) shows that protection of rightsof investors through courts, contributes significantly to the growth of a firm. Schiantarelli, Stacchini, and Strahan (2020) provide support to this view. They found that in the presence of weak enforcement of law, even solvent borrowers try to delay their debt repayment, hence the growth of firms is adversely affected.…”
Section: Variablesmentioning
confidence: 58%
See 2 more Smart Citations
“…A recent study by Miroshnychenko, bozziy and barontini (2019) shows that protection of rightsof investors through courts, contributes significantly to the growth of a firm. Schiantarelli, Stacchini, and Strahan (2020) provide support to this view. They found that in the presence of weak enforcement of law, even solvent borrowers try to delay their debt repayment, hence the growth of firms is adversely affected.…”
Section: Variablesmentioning
confidence: 58%
“…Bae and Goyal ( 2009) report that in inefficient judicial systems, recovery rates are lower. Recently, the findings of the study conducted by Schiantarelli, Stacchini, and Strahan (2020) in Italy show that borrowers selectively delay payment to banks already weakened by past bad loans while continuing to pay healthier banks.…”
Section: Demand Side View Of Improvement In Judicial Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…By lengthening the time to recover bad loans, court inefficiency might increase the stock of NPLs on banks' balance sheet. It could also change the incentives of creditors to repay their obligations (Schiantarelli et al, 2020), thereby affecting the flow of new NPLs. In the analysis, the stock of NPLs is approximated with a dummy variable which takes the value of one if there are some NPLs at the firm-bank match.…”
Section: The Main Dependent Variables In the Analysismentioning
confidence: 99%
“…The variation in courts enforcement has been exploited to address different research questions by Ponticelli and Alencar (2016) and Schiantarelli et al (2020). The first paper uses the differences in the functioning of Brazilian courts to analyze the effect of a reform of the Brazilian bankruptcy law on firms productivity and credit access.…”
mentioning
confidence: 99%